Spatial Suitability for Optimal Wind Energy Harvesting Site Selection in Misurata Municipality - Abdulati, Fatima Ahmed ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2025)
This study aimed to identify suitable locations for wind power generation and calculate their area using Geographic Information Systems (GIS) and spatial modeling techniques. A set of key indicators influencing the selection of wind farm sites was identified, including wind speed, slope gradient, distance from valleys, distance from the coastline, distance from airports, proximity to the electrical grid and main roads, and land use type. These indicators were spatially analyzed using ARC GIS 10.8 through one of its spatial analysis methods—Overlay Analysis. The study adopted both descriptive and analytical methodologies. The results revealed that the annual average wind speed in the study area exceeded 5 m/s at all locations, which meets the required threshold for project implementation. This indicates that Misrata Municipality is a promising region for future wind energy investments. The total area suitable for establishing wind farms was found to be 942.11 km², representing 16.751% of the study area.